Diversity of Purple Phototrophic Bacteria, Inferred from pufM Gene, within Epilithic Biofilm in Tama River, Japan - Hirose, Setsuko (Japanese Society of Microbial Ecology/The Japanese Society of Soil Microbiology, 2012)
The diversity of purple phototrophic bacteria in algae-dominated biofilm of a streambed in Tama River, Japan was investigated. Clone library analysis of the pufM gene encoding a subunit of the photochemical reaction center of purple bacteria detected 18 operational taxonomic units (OTUs) in several classes of Proteobacteria. Most of the OTUs showed less than 85% identity to the PufM amino acid sequences of known phototrophic bacteria. These results suggest that phylogenetically divergent and unknown purple phototrophic bacteria are present in the epilithic biofilm of the river.